P426 Association Between vedolizumab therapy outcome and Pre-treatment DUBLIN Score & CRP-Albumin Ratio in Ulcerative Colitis. (21st January 2022) - McCormick, E; Singh, P; Kevans, D
Abstract: Background: The DUBLIN score is a measure of ulcerative colitis (UC) inflammatory burden and is associated with clinical outcomes. A high CRP/albumin ratio (CAR) is associated with disease severity in IBD. The aim of our study was to evaluate if there was an association between vedolizumab therapy outcome and pre-treatment DUBLIN score and CAR in UC. Methods: 35 patients with UC initiating vedolizumab with available pre-treatment DUBLIN score and CAR data were identified. Baseline characteristics, biochemistry and endoscopic findings were defined by retrospective review. A previously validated DUBLIN score threshold of ≥3 and CAR threshold >0.6 were utilised to categorise patients with high inflammatory burden. Clinical response at, 3-months and corticosteroid-free remission at, 6-months were recorded. The association between, 3-month clinical response and, 6-month remission rates & pre-treatment DUBLIN score and CAR ratio were evaluated. P values <0.05 were considered significant. Results: Baseline characteristics of the study cohort: age [median, range], 53 [19 -87] years;, 60% male; disease duration [median, range], 11 [2–41] years. A pre-treatment DUBLIN score ≥3 and CAR >0.6 were observed in, 65% and, 51% of patients respectively., 3-month clinical response and, 6-month corticosteroid-free remission rates were observed in, 79% and, 67% of the cohort respectively. There was no significant difference between rates of, 3-month clinical response and, 6-month corticosteroid-free remission comparing high and low pretreatment DUBLIN score and CAR groups, p=0.59 and p=0.16 respectively. Conclusion: Vedolizumab was an effective therapy in patients with a significant inflammatory burden assessed by DUBLIN score and CAR. Pre-treatment DUBLIN score and CAR were not associated with therapy outcome.